Mechanical Design and Analysis of a Unilateral Cervical Spinal Cord Contusion Injury Model in Non-Human Primates - Sparrey, Carolyn J. (J Neurotrauma, 2016)
Non-human primate (NHP) models of spinal cord injury better reflect human injury and provide a better foundation to evaluate potential treatments and functional outcomes. We combined finite element (FE) and surrogate models with impact data derived from in vivo experiments to define the impact mechanics needed to generate a moderate severity unilateral cervical contusion injury in NHPs (Macaca mulatta). Three independent variables (impactor displacement, alignment, and pre-load) were examined to determine their effects on tissue level stresses and strains. Mechanical measures of peak force, peak displacement, peak energy, and tissue stiffness were analyzed as potential determinants of injury severity. Data generated from FE simulations predicted a lateral shift of the spinal cord at high levels of compression (>64%) during impact. Submillimeter changes in mediolateral impactor position over the midline increased peak impact forces (>50%). Surrogate cords established a 0.5 N pre-load protocol for positioning the impactor tip onto the dural surface to define a consistent dorsoventral baseline position before impact, which corresponded with cerebrospinal fluid displacement and entrapment of the spinal cord against the vertebral canal. Based on our simulations, impactor alignment and pre-load were strong contributors to the variable mechanical and functional outcomes observed in in vivo experiments. Peak displacement of 4 mm after a 0.5N pre-load aligned 0.5–1.0 mm over the midline should result in a moderate severity injury; however, the observed peak force and calculated peak energy and tissue stiffness are required to properly characterize the severity and variability of in vivo NHP contusion injuries.